2013
DOI: 10.1021/ma401014h
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Initiation of the Polymerization Mechanism and Network Development in Aromatic Polybenzoxazines

Abstract: Three bis-benzoxazine monomers based on the aniline derivatives of bisphenol A (BA-a), bisphenol F (BF-a), and 3,3′-thiodiphenol (BT-a) are examined using a variety of spectroscopic, chromatographic, and thermomechanical techniques. The effect on the polymerization of the monomers is compared using two common compounds, 3,3′-thiodiphenol (TDP) and 3,3′-thiodipropionic acid (TDA), at a variety of loadings. It is found that the diacid has a greater effect on reducing the onset of polymerization and increasing cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
74
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 29 publications
13
74
0
Order By: Relevance
“…This suggests the prevalence of a different cured polymer network (perhaps relating to the co-reaction mechanism) as the BPA content increases. In a previous publication, we examined the acceleration of the ring opening reaction of the BA-a monomer using active hydrogen donors 40 , such as thiodiphenol (1-25 mol%). The DSC profile recorded for the blend of BA-a containing 25 wt% BPA in this work is similar to the profile of the BA-a containing 12 mol% thiodiphenol.…”
Section: Methodology For Molecular Modelling the Molecular Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests the prevalence of a different cured polymer network (perhaps relating to the co-reaction mechanism) as the BPA content increases. In a previous publication, we examined the acceleration of the ring opening reaction of the BA-a monomer using active hydrogen donors 40 , such as thiodiphenol (1-25 mol%). The DSC profile recorded for the blend of BA-a containing 25 wt% BPA in this work is similar to the profile of the BA-a containing 12 mol% thiodiphenol.…”
Section: Methodology For Molecular Modelling the Molecular Modellingmentioning
confidence: 99%
“…4). Evidently as the BPA content is increased not only does the initial stage of the 11 polymerisation exotherm move to a lower temperature regime (the initial ring opening is known to be accelerated by active hydrogen donors 40 , but the breadth of the exotherm grows to reveal an increasingly complex peak comprising at least three processes. Rheological analysis was also performed on the uncured blends in parallel with the DSC measurements.…”
Section: Methodology For Molecular Modelling the Molecular Modellingmentioning
confidence: 99%
“…7 Benzoxazines are typically synthesized from phenol, amine, and formaldehyde via a Mannich reaction. [19][20][21][22][23][24][25][26][27][28][29][30][31][32] To cure 1,3-benzoxazines, thermally accelerated polymerization has been the main focus for most researchers for a long time. There have been a lot of successful reports on the development of benzoxazine monomers to improve material performance or expand the range of their applications, 8 for example, lowering the polymerization temperature by introducing hydroxyl, 9,10 acetylene, 11,12 N-allyl, 13 and carboxylic acid groups 14 to benzoxazine compounds, increasing the cross-linking density by the incorporation of polymerizable groups, [15][16][17] improving ame retardancy by phosphorylation of the cured products, 18 and others.…”
Section: Introductionmentioning
confidence: 99%
“…29 Polybenzoxazines possess many attractive properties such as no small molecule 30 byproduct generated and near-zero shrinkage during curing, high modulus and high 31 char yield, low water uptake, excellent dielectric properties and extremely rich 32 flexibility of molecular design [6][7][8][9][10][11][12]. These characters make them promising 33 candidates in many applications like semiconductor encapsulations and composite 34 matrix resins, etc.…”
mentioning
confidence: 99%
“…From another point of view, benzoxazines can serve as 47 hardeners for epoxy [26,27]. 48 In the past decades, the curing kinetics of benzoxazine has been extensively 49 investigated by non-isothermal DSC which is more precise and attractive to evaluate 50 the curing kinetic parameters in a relatively short period of time [19,26,[28][29][30][31]. It 51 was found that the curing reaction of benzoxazine was autocatalytic in nature.…”
mentioning
confidence: 99%